Correlation of surface-enhanced Raman scattering (SERS) with the surface density of gold nanoparticles: evaluation of the critical number of SERS tags for a detectable signal - Amendola, Vincenzo (Beilstein Journal of Nanotechnology, 2019)
The use of plasmonic nanotags based on the surface-enhanced Raman scattering (SERS) effect is highly promising for several applications in analytical chemistry, biotechnological assays and nanomedicine. To this end, a crucial parameter is the minimum number of SERS tags that allows for the collection of intense Raman signals under real operating conditions. Here, SERS Au nanotags (AuNTs) based on clustered gold nanoparticles are deposited on a substrate and analyzed in the same region using Raman spectroscopy and transmission electron microscopy. In this way, the Raman spectra and the surface density of the SERS tags are correlated directly, showing that 1 tag/µm2 is enough to generate an intense signal above the noise level at 633 nm with an excitation power of only 0.65 mW and an acquisition time of just 1 s with a 50× objective. The AuNT density can be even lower than 1 tag/µm2 when the acquisition time is extended to 10 s, but must be increased to 3 tags/µm2 when a 20× objective is employed under the same excitation conditions. In addition, in order to observe a linear response, it was found that 10 SERS AuNTs inside the probed area are required. These findings indicate that a better signal-to-noise ratio requires high-magnification optics, while linearity versus tag number can be improved by using low-magnification optics or a high tag density. In general the suitability of plasmonic SERS labels for ultrasensitive analytical and biomedical applications is evident.
Keywords: discrete dipole approximation (DDA); gold nanoparticles (AuNPs); nanotags; surface-enhanced Raman scattering (SERS); surface plasmon resonance (SPR)

Noble and Precious Metals - Properties, Nanoscale Effects and Applications - Bora, T. (Recent Developments on Metal Nanoparticles for SERS Applications, 2018)

(untitled) - Foti, A.; Barreca, F.; Fazio, E.; D’Andrea, C.; Matteini, P.; Maragò, O. M.; Gucciardi, P. G. (Beilstein J. Nanotechnol., 2018)

(untitled) - Zanchi, C.; Lucotti, A.; Tommasini, M.; Trusso, S.; de Grazia, U.; Ciusani, E.; Ossi, P. M. (Beilstein J. Nanotechnol., 2015)

(untitled) - Grosu, A. L.; Weber, W. A.; Franz, M.; Stärk, S.; Piert, M.; Thamm, R.; Gumprecht, H.; Schwaiger, M.; Molls, M.; Nieder, C. (Int. J. Radiat. Oncol., Biol., Phys., 2005)

(untitled) - Le Ru, E. C.; Blackie, E.; Meyer, M.; Etchegoin, P. G. (J. Phys. Chem. C, 2007)

(untitled) - Gürdal, E.; Dickreuter, S.; Noureddine, F.; Bieschke, P.; Kern, D. P.; Fleischer, M. (Beilstein J. Nanotechnol., 2018)

(untitled) - Wang, A.; Kong, X. (Materials, 2015)

(untitled) - Moskovits, M. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Meixner, A. J.; Leiderer, P. (Beilstein J. Nanotechnol., 2014)

(untitled) - McLintock, A.; Lee, H. J.; Wark, A. W. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Le Ru, E. C.; Galloway, C.; Etchegoin, P. G. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Vosgröne, T.; Meixner, A. J. (ChemPhysChem, 2005)

(untitled) - Shan, B.; Pu, Y.; Chen, Y.; Liao, M.; Li, M. (Coord. Chem. Rev., 2018)

(untitled) - Gandra, N.; Singamaneni, S. (Nanomedicine (London, U. K.), 2013)

(untitled) - Zavaleta, C. L.; Garai, E.; Liu, J. T. C.; Sensarn, S.; Mandella, M. J.; Van de Sompel, D.; Friedland, S.; Van Dam, J.; Contag, C. H.; Gambhir, S. S. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Tripp, R. A.; Dluhy, R. A.; Zhao, Y. (Nano Today, 2008)

(untitled) - Wang, Y.; Yan, B.; Chen, L. (Chem. Rev., 2013)

(untitled) - Amendola, V.; Meneghetti, M. (Adv. Funct. Mater., 2012)

(untitled) - Amendola, V.; Meneghetti, M.; Fiameni, S.; Polizzi, S.; Fracasso, G.; Boscaini, A.; Colombatti, M. (Anal. Methods, 2011)

(untitled) - Stanca, S. E.; Matthäus, C.; Neugebauer, U.; Nietzsche, S.; Fritzsche, W.; Dellith, J.; Heintzmann, R.; Weber, K.; Deckert, V.; Krafft, C.; Popp, J. (Nanomedicine (N. Y., NY, U. S.), 2015)

(untitled) - Narayanan, N.; Karunakaran, V.; Paul, W.; Venugopal, K.; Sujathan, K.; Kumar Maiti, K. (Biosens. Bioelectron., 2015)

(untitled) - Qian, X.; Peng, X.-H.; Ansari, D. O.; Yin-Goen, Q.; Chen, G. Z.; Shin, D. M.; Yang, L.; Young, A. N.; Wang, M. D.; Nie, S. (Nat. Biotechnol., 2008)

(untitled) - Stender, A. S.; Marchuk, K.; Liu, C.; Sander, S.; Meyer, M. W.; Smith, E. A.; Neupane, B.; Wang, G.; Li, J.; Cheng, J.-X.; Huang, B.; Fang, N. (Chem. Rev., 2013)

(untitled) - Vanhecke, D.; Rodriguez-Lorenzo, L.; Clift, M. J. D.; Blank, F.; Petri-Fink, A.; Rothen-Rutishauser, B. (Nanomedicine (London, U. K.), 2014)

(untitled) - Vermeulen, L. M. P.; Brans, T.; De Smedt, S. C.; Remaut, K.; Braeckmans, K. (Nano Today, 2018)

(untitled) - Radziuk, D.; Moehwald, H. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Allgeyer, E. S.; Pongan, A.; Browne, M.; Mason, M. D. (Nano Lett., 2009)

(untitled) - Qian, X. M.; Nie, S. M. (Chem. Soc. Rev., 2008)

(untitled) - Zavaleta, C. L.; Smith, B. R.; Walton, I.; Doering, W.; Davis, G.; Shojaei, B.; Natan, M. J.; Gambhir, S. S. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Wang, L.; O’Donoghue, M. B.; Tan, W. (Nanomedicine (London, U. K.), 2006)

(untitled) - Amendola, V.; Scaramuzza, S.; Litti, L.; Meneghetti, M.; Zuccolotto, G.; Rosato, A.; Nicolato, E.; Marzola, P.; Fracasso, G.; Anselmi, C.; Pinto, M.; Colombatti, M. (Small, 2014)

(untitled) - Tian, L.; Fei, M.; Tadepalli, S.; Morrissey, J. J.; Kharasch, E. D.; Singamaneni, S. (Adv. Healthcare Mater., 2015)

(untitled) - Bora, T.; Dousse, A.; Sharma, K.; Sarma, K.; Baev, A.; Hornyak, G. L.; Dasgupta, G. (Int. J. Smart Nano Mater., 2019)

(untitled) - Khlebtsov, B.; Pylaev, T.; Khanadeev, V.; Bratashov, D.; Khlebtsov, N. (RSC Adv., 2017)

(untitled) - Pilot, R. (J. Raman Spectrosc., 2018)

(untitled) - Driscoll, A. J.; Harpster, M. H.; Johnson, P. A. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Bohndiek, S. E.; Wagadarikar, A.; Zavaleta, C. L.; Van de Sompel, D.; Garai, E.; Jokerst, J. V.; Yazdanfar, S.; Gambhir, S. S. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Tran, V.; Thiel, C.; Svejda, J. T.; Jalali, M.; Walkenfort, B.; Erni, D.; Schlücker, S. (Nanoscale, 2018)

(untitled) - Zámbó, D.; Szekrényes, D. P.; Pothorszky, S.; Nagy, N.; Deák, A. (J. Phys. Chem. C, 2018)

(untitled) - Zaleski, S.; Wilson, A. J.; Mattei, M.; Chen, X.; Goubert, G.; Cardinal, M. F.; Willets, K. A.; Van Duyne, R. P. (Acc. Chem. Res., 2016)

(untitled) - Scaramuzza, S.; Zerbetto, M.; Amendola, V. (J. Phys. Chem. C, 2016)

(untitled) - Amendola, V. (J. Nanosci. Nanotechnol., 2015)

(untitled) - Amendola, V.; Meneghetti, M. (J. Phys. Chem. C, 2009)

(untitled) - Draine, B. T.; Flatau, P. J. (arXiv, 2010)

(untitled) - Draine, B. T.; Flatau, P. J. (J. Opt. Soc. Am. A, 1994)

(untitled) - Amendola, V.; Scaramuzza, S.; Agnoli, S.; Polizzi, S.; Meneghetti, M. (Nanoscale, 2014)

(untitled) - Goodman, J. J.; Flatau, P. J.; Draine, B. T. (Opt. Lett., 1991)

(untitled) - Scaramuzza, S.; Badocco, D.; Pastore, P.; Coral, D. F.; Fernández van Raap, M. B.; Amendola, V. (ChemPhysChem, 2017)

(untitled) - Herrmann, J. F.; Höppener, C. (Beilstein J. Nanotechnol., 2018)

(untitled) - Butet, J.; Bernasconi, G. D.; Martin, O. J. F. (Beilstein J. Nanotechnol., 2018)

(untitled) - Milekhin, A. G.; Kuznetsov, S. A.; Milekhin, I. A.; Sveshnikova, L. L.; Duda, T. A.; Rodyakina, E. E.; Latyshev, A. V.; Dzhagan, V. M.; Zahn, D. R. T. (Beilstein J. Nanotechnol., 2018)

(untitled) - Amendola, V.; Saija, R.; Maragò, O. M.; Iatì, M. A. (Nanoscale, 2015)

(untitled) - Kim, K. H.; Chae, S. S.; Jang, S.; Choi, W. J.; Chang, H.; Lee, J.-O.; Lee, T. I. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Kiesow, K. I.; Dhuey, S.; Habteyes, T. G. (Appl. Phys. Lett., 2014)

(untitled) - Lidorikis, E. (J. Quant. Spectrosc. Radiat. Transfer, 2012)

(untitled) - Jiao, J.; Wang, X.; Wackenhut, F.; Horneber, A.; Chen, L.; Failla, A. V.; Meixner, A. J.; Zhang, D. (ChemPhysChem, 2012)

Raman Spectroscopy for Chemical Analysis - McCreery, R. L. (Raman Microscopy and Imaging, 2005)